The Moderation of Health Motivation on The Adoption of Wearable Health Devices (WHD), Quantitative Study of Millennials in Indonesia - Eries Setiyawan; Daniel Tumpal Hamonangan Aruan (Lembaga Publikasi Ilmiah Nusantara, 2026)
The rapid growth of wearable health devices (WHD) has not been matched by equivalent adoption, particularly in emerging economies such as Indonesia. Previous studies have primarily focused on technological determinants, while the moderating role of health motivation in linking behavioral intention to actual usage remains underexplored. This study extends the Technology Acceptance Model (TAM) by integrating perceived product value and health motivation to explain WHD adoption among Indonesian millennials. A quantitative approach with a cross-sectional survey design was employed. Data were collected from 350 millennial respondents in Indonesia and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The measurement model assessment confirmed that all variables met the criteria for validity and reliability. The findings reveal that health motivation significantly moderates the relationship between intention to use and actual usage of WHD. Perceived compatibility, perceived technology accuracy, and perceived usefulness positively and significantly influence perceived product value. In addition, perceived product value significantly affects intention to use, while intention to use and health motivation significantly affect actual WHD usage. Conversely, perceived cost, perceived personal privacy, and social image do not significantly influence perceived product value. These results indicate that WHD adoption among Indonesian millennials is primarily driven by functional factors, including device compatibility with users’ lifestyles, technological accuracy, usefulness, perceived product value, and health motivation. This study contributes theoretically to the literature on health technology adoption and provides practical implications for WHD manufacturers in developing marketing strategies focused on product value and health motivation.